Genetic discontinuity in two high dispersal marine invertebrates in the northwest Atlantic - Anthony L. Einfeldt; Felix Zhou; Jason A. Addison (Canadian Science Publishing, 2017)
Oceanic circulation patterns shape both the distribution of species and spatial patterns of intraspecific genetic variation by influencing passively dispersed marine invertebrates. In the northwest Atlantic, strong and consistent currents at the mouth of the Bay of Fundy are expected to restrict dispersal in this region, but the relationship between populations of high dispersal species along the surrounding coastal regions has been largely underrepresented in the phylogeographic literature. We analyzed phylogeographic patterns in two intertidal invertebrates with high dispersal abilities, Tritia obsoleta (Mollusca: Gastropoda) and Macoma petalum (Mollusca: Bivalvia), between Cape Cod and the Gulf of St. Lawrence using mitochondrial DNA (mtDNA). Hierarchical analysis of molecular variance revealed population structuring among regions defined by circulation patterns, highly divergent lineages within M. petalum, and strong concordant genetic subdivision in both species between the Bay of Fundy and Gulf of Maine. Our results suggest that the gyre at the mouth of the bay is influential in restricting alongshore dispersal, allowing genetic divergence between regions to arise through genetic drift. These findings are concordant with biogeographic and phylogeographic studies of other marine organisms, suggesting that the genetic isolation of widely distributed species may be a common feature of intertidal invertebrate communities in the Bay of Fundy.